2004
DOI: 10.1007/s00266-004-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgery for Crooked Nose: An Objective Method of Evaluation

Abstract: It is difficult to achieve satisfactory results in the correction of crooked noses. The angle measurement method using the Scion Image computer program may be helpful in evaluating the effectiveness of different surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 3 publications
6
64
0
4
Order By: Relevance
“…The natural force existing in the cartilaginous structures and soft tissue (shortened muscles and connective tissue on the crooked side) continue to act on the nose submitted to rhinoplasty and makes it difficult to achieve an excellent result in the postoperative time. Another factor which may cause the nose to return to its crooked shape is the incomplete correction of the deviated nasal septum 3,9,10 . In our sample, septoplasty associated with rhinoplasty was done in 90% of the patients, a similar result to another study in which 89% of the patients were submitted to septoplasty 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The natural force existing in the cartilaginous structures and soft tissue (shortened muscles and connective tissue on the crooked side) continue to act on the nose submitted to rhinoplasty and makes it difficult to achieve an excellent result in the postoperative time. Another factor which may cause the nose to return to its crooked shape is the incomplete correction of the deviated nasal septum 3,9,10 . In our sample, septoplasty associated with rhinoplasty was done in 90% of the patients, a similar result to another study in which 89% of the patients were submitted to septoplasty 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the crooked nose correction requires the use of more elaborated techniques, our study showed that 68.4% of patients submitted to rhinoplasty to correct a crooked nose obtained excelled postoperative results (satisfaction ≥75), as depicted on Table 2. Okur et al, analyzed deviated angle measures from an objective method (result quantification based on a computer program), and considered that the closer the postoperative angle was from the ideal angle, the greater was the surgery's success rate 3 . They reported that 66.7% of the patients reached good or excellent results (result ≥70) 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correction of crooked noses is considered one of the most di cult septo-pyramidal surgical procedures (9) and several techniques have been proposed (10)(11)(12)(13) . SRD improves frontally, deviated, nasal crests by 64.3% (Table 1) Whilst 65% of nostrils were asymmetric before surgery, 52% had become symmetric afterwards.…”
Section: Discussionmentioning
confidence: 99%